HUBUNGAN ANTARA HIPERURIKEMIA DENGAN MICROALBUMINURIA PADA MASYARAKAT DESA LEGIAN KUTA BALI - Halim, Abd.; -, Kambayana; Raka Putra, Tjokorda (journal of internal medicine, 2012)
Microalbuminuria has been linking to cardiovascular (CV) risk in patients with diabetes or hypertension in unselected general population. Serum Uric Acid (UA) is an emerging novel risk factor for CV disease. The aim of our study was to evaluate the correlations between hyperucemia and microalbuminuria in the adult Legian Kuta Village population. We selected eligible 136 participants of adult (>18 years old) in Legian Kuta village who agreed to participate. We excluded diabetes mellitus, hypertension, urinary tract infection, and fever. We measured total cholesterol, HDL, LDL-cholesterol, triglyseride, fasting and 2-hour post prandial blood sugar, serum creatinine, serum uric acid, systolc-diastolic blood pressure and microalbuminuria (Urinary Albumin/Creatinine Ratio, ACR). The prevalence of hyperuricemia in our study was 16.9 % while microalbuminuria was 5.1 % (ACR 30 ! 299  g/mg creatinine) and macroalbuminuria 1.5% (ACR > 300  g/mg creatinine). Hyperuricemia and obesity signiÞ cantly correlated with microalbuminuria by Bivariate Analysis Spearmanrho correlation r = 0.274, p = 0.001; r = 0.178, p = 0.038 (p < 0.05) respectively. Age, sex, smoking, total cholesterol, LDL, HDL and triglyseride were not signiÞ cantly correlated with microalbuminuria (p > 0.05). In a stepwise multiple logistic regression model, hyperuricemia to microalbuminuria remained signiÞ cantly correlated with R Square 0.280 and prevalence ratio 7.90; p = 0.013; 95% CI 1.54 ! 40.60. Obesity was not signiÞ cantly correlated with microalbuminuria p = 0.161; 95% CI 0.59 ! 23.03. Our study showed hyperuricemia was signiÞ cantly correlated, as independent predictors to microalbuminuria.
Keywords: hyperuricemia, microalbuminuria, adult Legian Kuta population PENDAHULUAN Saat ini hiperurisemia dihubungkan dengan hipertensi dan